Thermal monitoring as a method for estimation of technical state of digital devices - Yu. N. Lavrich (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Requirements to the reliability level of modern element base are so high that traditional methods of assessing the technical condition of electronics become ineffective, the modern theory of reliability has almost no practical applications, and reliability index does not reflect the true state of an electronic device due to an insufficient amount of information received during testing of electronic devices. The majority of modern electronics are limitedly easy-to-test. They are equipped with small number of tools for direct measurement that leads to a delayed troubleshooting and the inability to take measures efficiently. Despite the fact that new generations of electronics use modern components and new design technologies, their performance is still defined by two states — serviceability or failure, and the failure still happens unexpectedly. We may note, that failure is an uncontrolled result of an irreversible degradation process, taking place in time and having appropriate time parameters, but it's not the critical act. Research of various structural and hierarchical levels of functional units of digital electronics show that temperature control can be used for automatic condition monitoring of such devices in real time. As a generalized control parameter, it is advisable to use the temperature of the case of the element, and the case itself — as a generalized point.